PENGARUH PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP KECERDASAN INTERPERSONAL ANAK USIA 5-6TAHUN DI TK PERTIWI KOTA PEKANBARU - Khairatni, Marsalina; Risma, Devi; solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on observations that have been done by researchers on children aged 5-6 years in TK Pertiwi Pekanbaru City still found some problems interpersonal intelligence. Such us, there are still children who are likes to tease his friend, there are still children who are often speak disrespectfully, there are still children who are let his freand cry or be, there are still children who are does not lend the goods he owns to friends who , there are still children who are can’t wait in wait, there are still children who are choise in friends. This research is purposed for to know the influence using the cooperative learning type of team games tournament (TGT) to ability of interpersonal intelligence children aged 5-6 years in TK Pertiwi Pekanbaru City. This research is experiment research using one group design with pretest and posttest. The sample that used is 16 people in this research. File accumulation’s technique that used is observation. Technique of data analysis using t-test test by using program of SPSS 20.0. The research hypothesis is that there is a significant influence on children's writing ability after team games tournament (TGT) activities. To find the hypothesis accepted or rejected based on data SPSS 20.0 can be seen tcount ꞊13,313 is bigger than ttable ꞊ 2,132 (13,313 > 2,132). Thus Ho is rejected and Ha accepted which means there is a significant difference between before and after doing experimentation by team games tournament (TGT) activities. The results of this study also see the effect of team games tournament (TGT) activities use on interpersonal intellegence of children aged 5-6 years. This can be known from the influence of the use of team games tournament (TGT) activities based on calculation using Gain formula that is equal to 30,22% is in the medium category and 69,78%influenced by other factors.Key words: interperonal intelligence, team games tournament (TGT) aktivities